Reintrodução de cervos-do-pantanal (Blastocerus dichotomus): uso do espaço e área de vida dos animais - Figueira, Cassio José Montagnani (2002)
Eleven adult marsh deers derived from the Porto Primavera population were reintroduced in two areas of São Paulo State at the end of 1998: Continental farmland (Colômbia - North São Paulo) and Jataí Ecological Station (Luís Antônio - Northeast São Paulo). The animals were radio tagged and daily monitored to survey space utilization and home-hange. Six marsh deers were reintroduced at Continental farmland (two males and four females) and surveyed from October until December 1998. The animals came to death in one to thirty days after the releases and a female disappeared in twenty days after its release probably because hunters activity. The surveys about space utilization and home-hange were unfeasible at Continental farmland by the limited survival of the animals. Five marsh deers were reintroduced at Jataí Ecological Station (two males and three females) and surveyed from December 1998 until April 2000. Two females came to death nearly two and four months after the releases and the rest remained alive during the study time. The survival of the animals at Jataí Ecological Station allowed surveys about home-range and space utilization in that area.